UKRAINE INFRASRUCTURE POST-WAR RECOVERY - AMOSHA, Oleksandr; CHEREVATSKYI, Danylo; AMOSHA, Olena; KVILYNSKYI, Oleksii (Journal of European Economy, 2024)
The importance of infrastructure, its state and types, the necessity of its post-war recovery according to European standards is shown. Creation of energy storage at closed Ukrainian and Polish mines, and their inclusion into the network of European continental energy system is offered. The basic principles of international project to create conveyor cross-border land portal between Ukraine and Poland have been developed to facilitate cross-border bulk cargo clearance. Pro posals are given to organise special branch that would use resources and materials recovered from civilian residential houses and industrial objects destroyed by belligerent activities. Special emphasis is on non-production social infrastructure. There are instances of its new elements creation, the need in which is imminent as a result of military activities, territory occupation, sufficient part of population’s temporary internal displacement and migration abroad, the need in education and requalification of labour force, workplaces creation, involving of international organizations with their experience to provide economy and infrastructure recovery. Top priority civilian activities to increase safety level in Ukraine are offered. JEL: О011.